Impact of oral health on the quality of life of young people in confinement, Córdoba, Argentina: A mixed methods study. - María M. Barnetche; Lila S. Cornejo (Universidad de Concepción., 2017)
Introduction: Quality of life can be understood as the perception subjects have of their position in life in relation to their goals, expectations and concerns. Measuring and understanding the impact of oral health on the quality of life of people may contribute to the promotion of health and prevention of disease. The aim of this study was to evaluate the impact of oral health on the quality of life of young people in confinement. Methodology: Cross-sectional study with mixed approach. Adolescents between 14 and 18 years of age, confined in socio-educational juvenile detention centers in the Province of Córdoba, Argentina, were included in the study. After signing of informed consent, the OHIP-49 questionnaire was applied to 70 youngsters and 32 semi-structured interviews were conducted. Results: The OHIP-49 had a mean of 53.37±28.77, the dimensions with more impact were: functional limitation, physical pain and psychological discomfort. Confinement emerges as an amplifier of sensations and as a barrier for accessing palliative care. Regarding aesthetic aspects, subjects reported specific discomfort that does not always interfere with their self-esteem or relationship with peers. Conclusions: Young people perceive the impact of oral health on their quality of life from episodes of suffering, although not only because of pain, but also for aesthetic reasons. Confinement creates a particular context for sensations and resolutions on health-disease-care processes regarding oral health.